HISTOPATHOLOGICAL CLASSIFICATION OF CANINE LYMPHOMAS IN THE CASUISTRY OF THE VETERINARY PATHOLOGY LABORATORY OF UNIVERSITY OF SAN MARCOS (1996-2012) - Puicón N., Víctor (2014)
The aim of this study was to apply the criteria of the World Health Organization (WHO) in the histopathological classification of canine lymphoma on cases diagnosed from 1996 to 2012 at the veterinary pathology laboratory of San Marcos University, Lima, Peru. A total of 1778 reports of canine neoplasia were revised and 16 cases with histopathological diagnoses of canine lymphoma were studied. The following types of lymphoma were identified: diffuse large B cell lymphoma (7/16) (immunoblastic subtype [4/16], centroblastic subtype [2/16], rich subtype T cells [1/16]), mantle cell lymphoma (3/ 16), peripheral T-cell lymphoma not otherwise specified (2/16), precursor B/T lymphoblastic lymphoma (2/16), anaplastic large cell lymphoma (1/16) and mycosis fungoides (1/16).